2023
DOI: 10.1155/2023/6673773
|View full text |Cite
|
Sign up to set email alerts
|

Urea Split Application to Maize (Zea mays L.) Growth Stages of Medium Maturities, Influenced on Grain Yield and Parameter for Yield at Bako, East Wollega, Ethiopia

Megersa Debele,
Belay Taressa

Abstract: Appropriate timing of application can improve crop nutrient consumption efficiency. Maize production is still significantly below than its potential output, even though it is comparatively better than other main cereal crops. One of the main abiotic variables affecting crop growth is the timing of urea split application. Due to these gaps, an experiment was carried out at the Bako Agricultural Research Center during the 2019 and 2020 cropping seasons in order to ascertain the best time to apply urea split in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The morphology and distribution of maize leaves directly affect light interception by the canopy and the efficiency of photosynthetic utilization, thereby influencing yield formation [45]. Effective spikes and thousand kernel weight are key components of yield composition [46,47]. This study identified significant to highly significant positive correlations between the effective number of spikes, thousand kernel weight, and traits such as plant height, ear height, ear-to-plant height ratio, leaf length, leaf width, and chlorophyll content.…”
Section: Diversity Of Phenotypic Traits In Maize Promotes Selection O...mentioning
confidence: 99%
“…The morphology and distribution of maize leaves directly affect light interception by the canopy and the efficiency of photosynthetic utilization, thereby influencing yield formation [45]. Effective spikes and thousand kernel weight are key components of yield composition [46,47]. This study identified significant to highly significant positive correlations between the effective number of spikes, thousand kernel weight, and traits such as plant height, ear height, ear-to-plant height ratio, leaf length, leaf width, and chlorophyll content.…”
Section: Diversity Of Phenotypic Traits In Maize Promotes Selection O...mentioning
confidence: 99%